Metabolism of Sodium Pentosan Polysulphate in Man – Catabolism of Iodinated Derivatives - MacGregor, I R; Dawes, J; Paton, L; Pepper, D S; Prowse, C V; Smith, M (Thrombosis and Haemostasis, 1984)
An iodinated derivative of the heparin analogue SP54 has been prepared and used in conjunction with unlabelled SP54 to study the catabolism and organ distribution of this potential antithrombotic agent in healthy human volunteers. As observed previously with 125I-heparin, we found that the 125I-SP54 was rapidly cleared from the circulation, returning later in a desulphated form. Organ distribution studies with 123I-SP54 suggested that the liver and spleen were major sites of desulphation. Gel filtration and Polybrene binding showed the presence of sulphated macromolecular SP54 and desulphated macromolecular and depolymerised SP54 in post-injection urines. No depolymerised material was present in plasma suggesting depolymerisation occurs in the kidney.
Keywords: Heparin analogue; SP54; Metabolism; Iodinated derivatives; Organ distribution